Synthesis and Structural Characterization of a New Tetranuclear Nickel(II) Sulfato Complex Containing the Anionic Form of Di-2-Pyridyl Ketone Oxime. (6th April 2011) - Moushi, Eleni; Efthymiou, Constantinos G.; Perlepes, Spyros P.; Papatriantafyllopoulou, Constantina
Abstract : The preparation and crystal structure of a tetranuclear Ni(II) sulfato cluster containing the anion of di-2-pyridyl ketone oxime, (py)2 CNO −, are reported. Treatment of NiSO4 ·6H2 O with one equivalent of (py)2 CNOH and one equivalent of NEt3 in MeOH leads to the compound [Ni4 {(py)2 CNO}4 (SO4 )2 (MeOH)4 ] (1 ) in moderate yield. The metal ions are linked together by two 3.2111 and two 2.1110 (Harris notation) (py)2 CNO − ligands, as well as two 2.1100SO 4 2 - ions to create a rare metallacrown-type (12-MC-4) ring. Strong H-bond intermolecular interactions in1 lead to the formation of a 1D chain along thec axis. Characteristic IR bands are discussed in terms of the known structure of1 .